Functional loss of Ccdc151 leads to hydrocephalus in a mouse model of primary ciliary dyskinesia - Francesco Chiani; Tiziana Orsini; Alessia Gambadoro; Miriam Pasquini; Sabrina Putti; Maurizio Cirilli; Olga Ermakova; Glauco P. Tocchini-Valentini (The Company of Biologists, 2019)
Primary ciliary dyskinesia (PCD) is a genetically heterogeneous disorder affecting normal structure and function of motile cilia, phenotypically manifested as chronic respiratory infections, laterality defects and infertility. Autosomal recessive mutations in genes encoding for different components of the ciliary axoneme have been associated with PCD in humans and in model organisms. The CCDC151 gene encodes for a coiled-coil axonemal protein that ensures correct attachment of outer dynein arm (ODA) complexes to microtubules. A correct arrangement of dynein arm complexes is required to provide the proper mechanical force necessary for cilia beat. Loss-of-function mutations in CCDC151 in humans leads to PCD disease with respiratory distress and defective left-right body asymmetry. In mice with the Ccdc151Snbl loss-of-function mutation (Snowball mutant), left-right body asymmetry with heart defects have been observed. Here, we demonstrate that loss of Ccdc151 gene function via targeted gene deletion in mice leads to perinatal lethality and congenital hydrocephalus. Microcomputed tomography (microCT) X-ray imaging of Ccdc151-β-galactosidase reporter expression in whole-mount brain and histological analysis show that Ccdc151 is expressed in ependymal cells lining the ventricular brain system, further confirming the role of Ccdc151 dysfunction in hydrocephalus development. Analyzing the features of hydrocephalus in the Ccdc151-knockout animals by microCT volumetric imaging, we observe continuity of the aqueduct of Sylvius, indicating the communicating nature of hydrocephalus in the Ccdc151-knockout animals. Congenital defects in left-right asymmetry and male infertility have been also observed in Ccdc151-null animals. Ccdc151 gene deletion in adult animals results in abnormal sperm counts and defective sperm motility. This article has an associated First Person interview with the joint first authors of the paper.